(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers the problem of formation of motivational basis for teaching Russian as a foreign language. Motivation is a critical component in this process, ensuring its effectiveness. Motivation for learning is a rather complicated and ambiguous process of changing the relationship of personality, as a separate subject of study, and to the entire learning process. Motives or, in other words, the causes that stimulate human and motivating him to be active, in this case – to learn – can be very different. The decisive role in shaping the motivational basis of students in the study of Russian language belongs to the teacher, who should work not with the student «in general», but with a particular personality with his strengths and weaknesses, individual abilities and inclinations.